Purpose-driven marketing strategies - Štefancová, Ema; Bahles, Michael; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The aim of the bachelor's thesis was to analyze and evaluate the marketing strategies of three purpose-driven brands, how do they communicate with the customer and also present their purpose. Further research has shown that not all of the brands actually do prefer marketing their purpose, and some do not focus on activating it; however, they still promote themselves with it. The purpose positioning without action leads to a current wave of woke-washing, which, as research has indicated, pushes customers even further away from the purpose due to authenticity concerns.
Vedoucí práce: Michael Bahles
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses